2011
DOI: 10.1108/17579861111108581
|View full text |Cite
|
Sign up to set email alerts
|

Laser shock peening to improve the fatigue resistance of AA7050 components

Abstract: Purpose -Laser shock peening (LSP) is a process capable of introducing compressive residual stresses into a metallic component. The residual compressive stress field can extend deeper below the treated surface than that produced by conventional shot peening (SP). The effect of such deep compressive stress profile is expected to result in a significantly greater benefit in fatigue resistance after LSP compared to SP. The purpose of this paper is to examine this further. Design/methodology/approach -Residual str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 1 publication
1
15
0
Order By: Relevance
“…2. A complete description of all the samples involved in the broader research programme can be found in [5]. Two samples with the same geometry were laser shock peened by Metal Improvement Company (MIC), Earby, UK, with the same laser parameters but different patterns: the first one was laser peened over the upper face including the blend curved area and the lateral side as shown in Fig.…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…2. A complete description of all the samples involved in the broader research programme can be found in [5]. Two samples with the same geometry were laser shock peened by Metal Improvement Company (MIC), Earby, UK, with the same laser parameters but different patterns: the first one was laser peened over the upper face including the blend curved area and the lateral side as shown in Fig.…”
Section: Samplementioning
confidence: 99%
“…Laser Shock Peening (LSP) is a relatively new surface treatment technique which has been shown to improve fatigue life in several metal alloys including titanium alloy [1], steel [2] and several aluminium alloys for aerospace applications like AA2024 [3] and AA7050 [4,5]. In LSP a pulsed high-energy laser beam is fired onto a sample surface that is covered by a transparent layer (usually water): an opaque ablative layer (such as thin aluminium tape, or paint) is also often applied.…”
Section: Introductionmentioning
confidence: 99%
“…The higher depth of compressive residual stresses from LSP [11,75,87,88,90,100,104,112,149,170,171] made it a vital technique for such fatigue life improvement as compared to the conventional shot peening process. Furthermore, other contributing factors such as surface roughness [127] has been attributed to either the increase or decrease in fatigue life depending on the LSP processing conditions, such as the number of shocks [53].…”
Section: Effect Of Laser Shock Peeningmentioning
confidence: 99%
“…LSP investigation on the fatigue life improvement of components was the main reason at the early stage of process development, where cracks are delayed and their propagation is retarded [ 6 , 11 , 55 , 56 , 152 , 168 , 169 ]. The higher depth of compressive residual stresses from LSP [ 11 , 75 , 87 , 88 , 90 , 100 , 104 , 112 , 149 , 170 , 171 ] made it a vital technique for such fatigue life improvement as compared to the conventional shot peening process. Furthermore, other contributing factors such as surface roughness [ 127 ] has been attributed to either the increase or decrease in fatigue life depending on the LSP processing conditions, such as the number of shocks [ 53 ].…”
Section: Effect Of Laser Shock Peeningmentioning
confidence: 99%
“…21 Laser shock processing is a new surface treatment technique similar to shot peening. In recent years, several attempts have been made in the literature [22][23][24][25][26] for researching the influence of LSP. Some researches 27,28 show that LSP can also improve the fatigue resistance of metal film materials.…”
Section: H E a L I N G M E T H O Dmentioning
confidence: 99%